Examining Canadian Hospitals’ Support for Planetary Health Through the Implementation of Green Teams and Sustainability Offices - Kalogirou MR; Baumbusch J (Journal of Healthcare Leadership)
Maya R Kalogirou, Jennifer Baumbusch School of Nursing, University of British Columbia, Vancouver, BC, CanadaCorrespondence: Maya R Kalogirou, University of Alberta, College of Health Sciences, Faculty of Nursing, Edmonton Clinic Health Academy (ECHA), 11405 87 Avenue NW, Edmonton, AB, T6G 1C9, Canada, Email reshef@ualberta.caPurpose: Planetary health is the idea that human health and the health of our planet are inextricably linked. The healthcare sector promotes human health but has a significant impact on our natural world. In Canada, some hospitals are leading the way towards promoting planetary health in an increasingly challenging context. The purpose of this study was to understand how Canadian hospitals support planetary health, specifically through green teams and sustainability offices.Patients and Methods: People working in Canadian hospitals, either in sustainability offices or green teams, were invited to participate in this study. Participants completed an online survey and indicated if they would like to take part in a semi-structured interview via Zoom. Twenty-nine participants were interviewed and asked about how they supported planetary health and how their teams were integrated into the hospital setting. Interview transcripts were analyzed and data were summarized using thematic analysis. Demographic information was collected through the survey.Results: Three main themes were: 1) From grassroots to corporate: Green teams and sustainability offices. This theme defined, compared, and contrasted teams and offices; 2) Operationalizing this work: Five green team exemplars. The five teams were: 1) the single-person green team; 2) the health profession-specific green team; 3) the green team pilot project; 4) external partners supporting green teams; and 5) the “bottom up” meets “top down” green team; and 3) Paving the path forward and tracking success. This theme explored how teams used metrics and other broader indicators to understand success.Conclusion: This study examined the work of Canadian sustainability offices and green teams in the hospital setting. The former promoted planetary health from a “top-down” perspective while the latter did so from a “bottom-up” perspective. Teams that integrated both approaches were the most effective in promoting planetary health.Plain Language Summary: The health sector is harming the planet’s natural systems, and now there is a need for it to start promoting planetary health. Planetary health is the idea that human health and the health of our natural systems are inseparable, and promoting planetary health means delivering health services in a way that also reduces climate change, pollution, and biosphere integrity issues. Hospitals have responded by creating sustainability offices. Hospital employees have responded by striking up green teams. The work these offices and teams are doing are well-documented in some healthcare systems, but in Canada, not much is known. This study was done so that we could better understand how Canadian hospitals support planetary health, specifically through green teams and sustainability offices.We sent out surveys that collected preliminary information on participants; anyone working in a sustainability office or on a green team in a Canadian hospital. We then conducted interviews, and from those data, we identified three themes:From grassroots to corporate: Green teams and sustainability officesOperationalizing this work: Five green team exemplarsPaving the path forward and tracking successOverall, there are good reasons for Canadian hospitals to have both a sustainability office and a green team as they focus on slightly different planetary health initiatives. It is also a strength to have a “top-down” meets “bottom-up” approach to planetary health promotion, because when sustainability offices work together with green teams, or when leaders themselves are part of teams, they can target larger-scale, more impactful planetary health initiatives.Keywords: planetary health, hospitals, climate change, environmental sustainability, net zero